وصمة الذات كمنبئ بالألكسيثيميا النفسية لدى ضعاف السمع - ياسين، حمدي محمد; أحمد، زهرة العلا عثمان إسماعيل (رابطة الأخصائيين النفسيين المصرية, 2016)
Objectives: Study the possibility of predicting Psychogenic Alexithymia through Self-Stigma in a sample of hard-of-hearing, and detect variations of both according to age. \ Sample: 31 hard-of-hearing male adolescents who attend to El-Amal Technical secondary- preparatory Institute -Asyut city. \ Tools: Self-Stigma & Psychogenic Alexithymia Scales (Prepared by/ The Researcher). \ Results: Self-Stigma can predict Psychogenic Alexithymia. Self-Stigma varies according to age in favor of the age group (19-21) years. Psychogenic Alexithymia varies according to age in favor of the same group.
الأهداف: دراسة إمكانية التنبؤ بالألكسيثيميا النفسية من خلال وصمة الذات لدى عينة من ضعاف السمع والكشف عن مدى اختلاف كل منهما باختلاف العمر.\ العينة: 31 مراهقا من ضعاف السمع الملتحقين بمعهد الأمل الفني الثانوي-الإعدادي بنين بمدينة أسيوط. \ الأدوات: مقياسي وصمة الذات والألكسيثيميا النفسية (إعداد/الباحثة).\ النتائج: تستطيع وصمة الذات التنبؤ بالألكسيثيميا النفسية. تتباين وصمة الذات بتباين العمر لصالح الفئة العمرية(19-21) عاما تتباين الألكسيثيميا النفسية بتباين العمر لصالح نفس الفئة.
Keywords: وصمة الذات -- ضعاف السمع -- الألكسيثيميا النفسية